2005
DOI: 10.1007/s10551-005-4772-2
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Ethical Frameworks in Determining Behavioral Intention: A Comparison of the U.S. and Russia

Abstract: Using Reidenbach and Robin's ( Journal of Business Ethics 7, 871-879, 1988) multi-criteria ethics instrument, we carried out the first empirical test of Robertson and Crittenden's (Strategic Management Journal 24,[385][386][387][388][389][390][391][392] 2003) cross-cultural map of moral philosophies to examine what ethical criteria guide business people in Russia and the U.S. in their intention to behave. Competing divergence and convergence hypotheses were advanced. Our results support a convergence hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 22 publications
2
35
0
3
Order By: Relevance
“…Using data collected in three countries (Germany, Italy, and Japan), our research empirically examines these two competing viewpoints to determine their influence on an individual's choice of ethical framework in decisionmaking. Since the primacy of peers as referents seems to be embedded within a broader countryspecific, cultural context (Beekun et al, 2005), our first hypothesis suggests that both macro-and micro-level variables are significant influences on an individual's intention to behave ethically.…”
Section: Analysis Of Antecedents To Ethical Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data collected in three countries (Germany, Italy, and Japan), our research empirically examines these two competing viewpoints to determine their influence on an individual's choice of ethical framework in decisionmaking. Since the primacy of peers as referents seems to be embedded within a broader countryspecific, cultural context (Beekun et al, 2005), our first hypothesis suggests that both macro-and micro-level variables are significant influences on an individual's intention to behave ethically.…”
Section: Analysis Of Antecedents To Ethical Decision-makingmentioning
confidence: 99%
“…Kymlicka (1995) and Beekun et al (2005) assert that the strength of the identity relationship that exists between individuals and their cultural-national communities can make it difficult for individuals to integrate into other cultures: ''Cultural membership affects our very sense of personal identity and capacity. The connection between personal identity and cultural membership is suggested by a number of considerations....Why cannot members of a decaying culture simply integrate into another culture?...…”
Section: Analysis Of Antecedents To Ethical Decision-makingmentioning
confidence: 99%
“…Russia > USA (Beekun et al, 2005;Ahmed et al, 2003) South Africa > Germany (Pflug, 2008) Croatia > USA (Tavakoli et al, 2003) Taiwan > USA (Lu, 2001;Cherry et al, 2003) Spain > Mexico (Husted et al, 1996) Egypt > USA (Marta et al, 2003) Ukraine > USA (Kennedy & Lawton, 1996) Taiwan > Australia > USA (Allmon et al, 1997) X China > EU (Vittel and Patwardhan, 2008) El Salvador > USA = Canada (Chiasson et al, 1996) Malaysia > USA (Karande et al, 2000) India > USA (Kracher et al, 2002) India = China = Malaysia (Zabid & Ho, 2003;Zabid & Ibrahim, 2008) Philippines > USA (Vasquez et al, 2001) Chile > Australia (Robertson et al, 2002) Mexico > Spain (Husted et al, 1996) Malaysia > New Zealand (Goodwin & Goodwin, 1999) China > Australia (Tsui & Windsor, 2001) II USA = Canada > El Salvador (Chiasson et al, 1996) USA > Russia (Beekun et al, 2005;Ahmed et al, 2003) USA > Philippines (Vasquez et al, 2001) Norway > USA (Falkenberg, 1998) Germany > South Africa (Pflug, 2008) Australia > USA X USA > Egypt (Marta et al, 2003) USA > Taiwan (Lu, 2001;Cherry et al, 2003) USA > Ukraina (Kennedy & Lawton, 1996) USA > Norway (Falkenberg, 1998) USA > Brazil (Volkema and Fleury, 2002) USA ...…”
Section: 2happiness Predicted By the Modelmentioning
confidence: 99%
“…A "by product" of this first purpose will be a ranking of ethical approaches in terms of individual happiness as dependent of individual characteristics. Next, there is a huge psychological, social and economic literature aiming at motivating (for recent examples, Pflug, 2008;Lu, 2001) or at assessing (for recent examples, Welsch, 2003;Peirò, 2006;Inglehart et al, 2008;Heylighen and Bernheim, 2000;Haller and Hadler, 2006;Veenhoven, 2005;Hayo, 2007;Lelkes, 2006) the observed differences in happiness contents in different countries or cultures, on the one hand; on the other hand, at justifying (for recent examples, Robertson and Crittenden, 2003;Gossling, 2003;Jensen, 2008) or at measuring (for recent examples, Brammer et al, 2006;Franke andNadler, 2008, Forsyth et al, 2008;Guiso et al, 2003;Cherry et al, 2003;Beekun et al, 2005;Ahmed et al 2003;Singhapakdi et al, 2001;Karande et al, 2000;Tavakoli et al, 2003;Vasquez et al 2001;Volkema & Fleury, 2002;Lu & Gilmour, 2004;Robertson et al 2002;Zabid and Ho, 2003;Zabid and Ibrahim, 2008;Kracher et al, 2002;Vittel and Patwardhan, 2008;Marta et al, 2001;Blodgood et al, 2008) the observed differences in ethical approaches prevailing in different countries or cultures. The second purpose of this paper is to apply the analytical model to explain the observed differences in happiness in different countries or cultures in terms of the observed different ethical approaches prevailing in different countries or cultures, under very plausible assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rest's study, the ethical decision-making process consists of four steps: 1) awareness, or the recognition of a moral issue, 2) judgment, the determination of an ethical judgment about the moral issue, 3) intention, or deciding upon an action in accordance with the ethical judgment, and 4) behavior, engaging in the action [27]. Most ethical decision-making models have focused on the judgment step and researchers have employed moral philosophies to explain judgment [18].…”
Section: Ethical Decision-making Model In the Internet Contextmentioning
confidence: 99%